Method in the Study of Totemism - Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 2014)
"Method in the Study of Totemism" by Andrew Lang is a scientific publication written in the early 20th century. The book explores the concept of totemism, analyzing its various features and examining whether a normative form of totemism can be defined or described. Through a critical examination of existing theories, particularly in contrast to the views of other scholars, Lang seeks to establish a systematic approach to understanding the institutions and practices associated with totemic societies. In this work, Lang embarks on a detailed critique of existing definitions of totemism, highlighting the complexities and divergences among various cultures, notably between those in British Columbia and Australia. He addresses key characteristics such as exogamous clans, the derivation of clan names from totems, religious attitudes towards these totems, and the accompanying taboos. Lang contends that many features that might seem independent are deeply interconnected within a framework that recognizes an underlying unity among the diverse expressions of totemism. Overall, his study aims to clarify the essential characteristics of totemism and establish a coherent methodology for investigating this anthropological phenomenon. (This is an automatically generated summary.)
Release date is 2014-08-10
Produced by Marc D'Hooghe (Images generously made available by the Hathi Trust)
Keywords: Totemism